Women in the discourse of early modern Spain - Cammarata, Joan, 1950- (University Press of Florida, 2003)
''The questions and approaches ... really get my respect by the way they are argued. Some of these essays will spark controversy as to method; all of them will make changes in the way we teach the Spanish classics and in what classics we do teach.